2017
DOI: 10.1038/s41598-017-17250-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic polymorphisms in pTEN/AKT/mTOR signaling pathway genes with cancer risk: A meta-analysis in Asian population

Abstract: The pTEN/AKT/mTOR signaling pathways play a critical role in balancing cell proliferation, differentiation, and survival. Recent studies researched the associations of core genes in the pTEN/AKT/mTOR pathway polymorphisms with the cancer susceptibility; however, the results are inconclusive. Therefore, a systematically meta-analysis was performed to evaluate the association between the five SNPs (mTOR rs2295080 and rs2536, AKT1 rs2494750 and rs2494752, pTEN rs701848) and cancer risk by systematic review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Through phosphorylation, PI3K - AKT inhibits the activity of proapoptotic members while activating anti-apoptotic members. The reduction in PTEN expression indirectly stimulates PI3K - AKT activity, thereby contributing to oncogenesis in mammals ( Zhang et al, 2017c ). Our studies showed that exposure to 10 μM ZEA significantly upregulated the PI3K - AKT gene expression in the dGCs, implying that exposure to low concentrations of ZEA (10 μM) might increase the donkey’s risk for ovarian cancer via the PTEN / PI3K / AKT pathway by suppressing the expression of antitumor genes or by activating the expression of cancer-causing genes ( Zhang et al, 2017c ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through phosphorylation, PI3K - AKT inhibits the activity of proapoptotic members while activating anti-apoptotic members. The reduction in PTEN expression indirectly stimulates PI3K - AKT activity, thereby contributing to oncogenesis in mammals ( Zhang et al, 2017c ). Our studies showed that exposure to 10 μM ZEA significantly upregulated the PI3K - AKT gene expression in the dGCs, implying that exposure to low concentrations of ZEA (10 μM) might increase the donkey’s risk for ovarian cancer via the PTEN / PI3K / AKT pathway by suppressing the expression of antitumor genes or by activating the expression of cancer-causing genes ( Zhang et al, 2017c ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in PTEN expression indirectly stimulates PI3K - AKT activity, thereby contributing to oncogenesis in mammals ( Zhang et al, 2017c ). Our studies showed that exposure to 10 μM ZEA significantly upregulated the PI3K - AKT gene expression in the dGCs, implying that exposure to low concentrations of ZEA (10 μM) might increase the donkey’s risk for ovarian cancer via the PTEN / PI3K / AKT pathway by suppressing the expression of antitumor genes or by activating the expression of cancer-causing genes ( Zhang et al, 2017c ). Moreover, it was reported that decreased TGF β-mediated signaling might predispose an individual to develop cancer ( Pasche, 2001 ; Galliher et al, 2006 ; Jin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Signaling through phosphoinositide3-kinase (PI3K) and its downstream targets, AKT and mTOR, serves a key role in differentiation, proliferation and cell survival (24). Tumor cell proliferation is increased by activating the PI3K/AKT/mTOR signaling pathways (Fig.…”
Section: Mir-21 and The Akt/mtor Signaling Pathwaymentioning
confidence: 99%
“…Inhibition of the PI3K (phosphatidylinositol 3-kinase)/AKT/mTOR signaling pathway is employed in therapeutic approaches for certain cancer types [11]. Two polymorphisms, rs2295080 and rs2536, have been identified in the human mTOR gene, mapping to chromosome 1p36.22 [12][13][14][15]. In the present study, we are interested in evaluating the possible effect of the two polymorphisms on the susceptibility to different cancers through a series of analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike four previously reported meta-analyses [13][14][15][16], this meta-analysis features newly published articles, and we utilized a different strategy for a comprehensive analysis. Three factors, including cancer type, genotyping method and control source, were considered for the subgroup analyses.…”
Section: Introductionmentioning
confidence: 99%